Humanização na Atenção Primária à Saúde no contexto da pandemia de Covid-19 - Arraes, José Diêgo Bezerra (2023)
Introduction: The COVID-19 pandemic has highlighted the strengths, but also the weaknesses that already exist in the different levels of care of the Unified Health System (SUS). In Primary Health Care (PHC), one of the challenges is the fulfillment of its essential attributes, however, there is also concern about the implementation of the guidelines of the National Humanization Policy (PNH), namely: welcoming, ambience, participatory management, defense of users' rights, appreciation of the worker and expanded clinic. Objective: To analyze compliance with PNH guidelines in PHC during the COVID-19 pandemic, from the user's point of view. Methods: Qualitative, exploratory and descriptive study, carried out with users assisted by the Family Health Strategy (ESF) in the municipality of Brejo Santo/CE. The research meets the criteria of resolution n° 466/12 of the National Health Council and was appreciated by the Research Ethics Committee (CEP) of the Faculty of Health Sciences of Trairi (FACISA)/Federal University of Rio Grande do Norte (UFRN ), having obtained a favorable opinion from nº 5.538.037/2022. The collection technique was a semi-structured interview, guided by a script prepared by the research team. The study included users aged 18 years or over, registered in the ESF of the aforementioned municipality for at least two years. Those users who had flu signs or symptoms at the time of the interview were excluded, following the health recommendations adopted during the pandemic. Sampling was carried out for convenience, considering the period established for data collection (between September and December 2022), so that a total of 23 participants was reached. Results: Data were processed using the Iramuteq software and submitted to thematic content analysis. The Descending Hierarchical Classification revealed six classes that originated the thematic categories, namely: "Reception and access in the ESF"; "Ambience and appreciation of the worker as a health service qualification strategy"; and "The importance of co-management and defense of the rights of SUS users". Conclusion: During the COVID-19 pandemic, access to care was maintained, through necessary adaptations due to the health context experienced at the time of collection. Although some users are unaware of the SUS user rights booklet, which can cause weaknesses in popular participation, it was demonstrated, in general, that there was respect for compliance with the PNH guidelines in these services. It was interpreted that welcoming and ambience are guidelines that appear in the speeches through other terms, however, guidelines such as co-management and expanded clinic were not identified. This fact leads us to believe that, despite the many advances in recent years, the full realization of humanization in PHC is still a challenge for many teams, a path that can be followed through the strengthening of the various care technologies, which involve communication, empathy, strengthening the bond, valuing knowledge and proper use of the resources available for these services.